The role of maternal psychosocial perceptions in parent-training programs: a preliminary randomized controlled trial. Issue 2 (6th March 2020) - ALPER, Rebecca M.; HURTIG, Richard R.; MCGREGOR, Karla K.
Abstract: Parent–child interaction is critical for early language and literacy development. Parent training programs have proliferated to support early interactions. However, many environmental and psychosocial factors can impact the quality of parent–child language and literacy interactions as well as training program outcomes. This preliminary randomized controlled trial examined maternal perceived self-efficacy and locus of control during a language and literacy parent training program. Thirty mother–child dyads (mother age 21–40; children 2;6–4;0) were assigned in parallel to the training or control group. The training was efficacious for mothers and children – training-group dyads made significantly greater gains in maternal strategy use, responsivity, and child print awareness than the control group. Gains were maintained one month post-training. Children whose mothers had more external baseline control perceptions identified significantly fewer print targets at baseline and made greater gains than those with more internal control perceptions. Future directions and implications are discussed.